FACTOR ANALYSIS FRAUD PREVENTION PROCUREMENT OF GOODS AND SERVICES IN RSUD BENDAN - Rima Devaluasi Hindrianti; Hijroh Rokhayati (Neraca, 2024)
This study aims to examine the effects of pressure, internal control, and organizational commitment on fraud in the procurement process at RSUD Bendan, Pekalongan City. The independent variables tested are pressure, internal control, and organizational commitment, with organizational commitment serving as a moderating variable and fraud as the dependent variable. The population of this study includes all employees of RSUD Bendan, with a sample consisting of employees involved in the procurement of goods and services. The sampling technique used in this study is purposive sampling. Data analysis is conducted using Partial Least Squares (PLS). The results of hypothesis testing indicate that pressure and organizational commitment affect fraud, while internal control does not have effect on fraud. Additionally, organizational commitment strengthens the relationship between pressure and internal control with fraud. The implication of this research is that RSUD Bendan should improve internal control in the procurement of goods and services   REFERENCE Albrecht, W. S., Albrecht, C. O., Albrecht, C. C., & Zimbelman, M. F. (2019). Instructor solutions manual: Fraud examination (6th ed., pp. 1–14). Cengage Learning. www.cengage.com/global. Bendan Hospital. (2017). Profil Rumah Sakit Umum Daerah Bendan. https://rsudbendan.pekalongankota.go.id/halaman/profil-rsud-bendan.html Cressey, D. R. (1950). The criminal violation of financial trust. American Sociological Review, 15(6), 738. https://doi.org/10.2307/2086606 Dessler, G. (2011). Human resource management. Pearson Education Limited, Upper Saddle River. Farida, S. N. (2017). Analisis pengaruh fraud diamond, personal attitude dan effectiveness of internal control terhadap tendensi kecurangan karyawan pada dealer otomotif di wilayah Jombang. Thesis. Universitas Islam Negeri Maulana Malik Ibrahim Malang. Fitri, F., & Nadirsyah. (2019). Pengaruh tekanan (pressure), kesempatan (opportunity), rasionalisasi (rationalization), dan kapabilitas (capability) terhadap kecurangan pengadaan barang/jasa di Pemerintahan Aceh dengan pemoderasi budaya etis organisasi. Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 4(3), 412–427. https://doi.org/10.24815/jimeka.v5i1.15437 Hadi, M., Ariyanti, R., & Notoatmojo, M. I. (2021). Pengaruh pengendalian internal dan komitmen organisasi dalam pencegahan fraud pengadaan barang (studi kasus pada RSUD Bendan Kota Pekalongan). Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 4(1), 21. https://doi.org/10.32497/akunbisnis.v4i1.2795  Ikatan Akuntansi Indonesia. (2001). Standar profesional akuntan publik. Jakarta: Salemba Empat.  Indonesian Corruption Watch. (2013). Laporan akhir tahun ICW 2013. Annual Report, 53(9), 287. Irwan, & Adam, K. (2015). Metode Partial Least Square (PLS) dan terapannya (Studi kasus: analisis kepuasan pelanggan terhadap layanan PDAM Unit Camming Kab. Bone). Jurnal Teknosains, 9(1), 53–68. Karvarino. (2020). Korupsi pengadaan rumah sakit, negara rugi Rp4,8 miliar. Gatra.Com. https://www.gatra.com/news-465901-hukum-korupsi-pengadaan-rumah-sakit-negara-rugi-rp48-miliar.html Karyono. (2002). Fraud auditing. The Winners, 3(2), 150–160. https://doi.org/10.1108/02686909810198724 Muhammad, R., & Ridwan. (2017). Pengaruh kesesuaian kompensasi, penerapan sistem informasi akuntansi, dan efektivitas pengendalian internal terhadap kecurangan akuntansi studi pada Bank Perkreditan Rakyat (BPR) di Kota Banda Aceh. Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi (JIMEKA), 2(4), 136–145. Mardiastuti, A. (2017). Terbukti korupsi alkes, Ratu Atut divonis 5,5 tahun penjara. Detik.Com. https://news.detik.com/berita/d-3567351/terbukti-korupsi-alkes-ratu-atut-divonis-5-5-tahun-penjara Meyer, J. P., & Allen, N. J. (1991). A three-component conceptualization of organizational commitment. Human Resource Management Review, 1(1), 108–135. https://doi.org/10.1057/9780230501997_5 Mustikasari, P. (2013). Faktor-faktor yang mempengaruhi fraud di sektor pemerintahan Kabupaten Batang. Accounting Analysis Journal (AAJ), 2(1), 250–258. Mowday, R. T., & Steers, Ri. M. (1979). The measurement of organizational commitment. Journal of Vocational Behavior, 14, 224–247. https://doi.org/10.1016/0041-008X(75)90174-X Pangestika, F. (2016). Pengaruh pengendalian internal, good governance, dan komitmen organisasi terhadap kinerja pegawai Bidang Keuangan Pemerintah Daerah Kabupaten Temanggung. Thesis. Universitas Negeri Yogyakarta. Yogyakarta.  Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah. (2021). Peraturan Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah Republik Indonesia No. 5 tahun 2021 tentang Pedoman Pengadaan Barang/Jasa yang Dikecualikan pada Pengadaan Barang/Jasa Pemerintah. https://jdih.lkpp.go.id/regulation/peraturan-lkpp/peraturan-lkpp-nomor-5-tahun-2021 Pramesti, M. A. D., Sunarsih, N. M., & Dewi, N. P. S. (2020). Pengaruh pengendalian internal, komitmen organisasi, dan kompensasi dalam pencegahan fraud pengadaan barang pada Rumah Sakit Umum Daerah Kabupaten Badung Mangusada. Jurnal Kharisma, 2(2), 78–95.  Robbins, S.P. (2001) Organizational behavior. 9th edition, Prentice-Hall, Inc., New York. Skousen, C. J., Smith, K. R., & Wright, C. J. (2008). Detecting and predicting financial statement fraud: the effectiveness of the Fraud Triangle and SAS no.99. In Corporate Governance and Firm Performance (Advances in Financial Economics) (Leeds, Issue 99). Emerald Group Publishing Limited.  Sopiah. (2008). Budaya organisasi, komitmen organisasional pimpinan dan pengaruhnya terhadap kepuasan kerja dan kinerja karyawan bank. Jurnal Keuangan dan Perbankan, 12(2), 308–317. The Committee of Sponsoring Organizations of the Treadway Commission (COSO). (2013). Internal Control—Integrated Framework.  Utaminingsih, N. S., Chariri, A., & Januarti, I. (2020). Control effectiveness and fraud: Evidence in Indonesia cooperative. International Journal of Scientific and Technology Research, 9(2), 2856–2859. Yayasan Penabulu. (2017). Panduan pengajaran mengelola keuangan BLUD. Direktorat Jenderal Perimbangan Keuangan (DJPK) Kementerian Keuangan Republik Indonesia. Yuniarti, R. D. (2017). The effect of internal control and anti-fraud awareness on fraud prevention (A survey on inter-governmental organizations). Journal of Economics, Business & Accountancy Ventura, 20(1), 71. https://doi.org/10.14414/jebav.v20i1.626 Zulkarnain, R. M. (2013). Analisis faktor yang mempengaruhi terjadinya fraud pada Dinas Kota Surakarta. Accounting Analysis Journal, 2(2), 457–465. http://journal.unnes.ac.id/sju/index.php/aaj